Method of constructing smartflow application based on Web services - LI Hui; CUI Li-zhen; WANG Hai-yang (Tongxin xuebao)
A new service-oriented process pattern——smartflow as well as the just-in-time construction of smartflow was proposed.Firstly,smartflow description framework（SfDF）,which was the semantic description cornerstone of smartflow, was put forward.Based on the SfDF,satisfied Web services were discovered.The smartflow model was constructed by using a algorthim based on traveling salesman problem.The feasibility of the method proposed is verified in smart travel platform.